2006
DOI: 10.1111/j.1467-842x.2006.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for preterm, low birth weight and small for gestational age birth in urban Aboriginal and Torres Strait Islander women in Townsville

Abstract: Objectives: To assess the characteristics of Indigenous births and to examine the risk factors for preterm (<37 weeks), low birth weight (<2,500 g) and small for gestational age (SGA) births in a remote urban setting. Design: Prospective cohort of singleton births to women attending Townsville Aboriginal and Islander Health Services (TAIHS) for shared antenatal care between 1 January 2000 and 31 December 2003. Main outcome measures: Demographic, obstetric, and antenatal care characteristics are described. Risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
59
2
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 29 publications
14
59
2
4
Order By: Relevance
“…20,21,24,26,27 We observed lesser proportion of lbw babies among hypertensive mothers which was contrary to the findings showed in other studies. 23,24,25 We could not explain this findings because scientifically it is natural that pregnancy induced hypertension resulted reduced placental perfusion thereby increased chance of lbw babies.…”
Section: Discussioncontrasting
confidence: 57%
“…20,21,24,26,27 We observed lesser proportion of lbw babies among hypertensive mothers which was contrary to the findings showed in other studies. 23,24,25 We could not explain this findings because scientifically it is natural that pregnancy induced hypertension resulted reduced placental perfusion thereby increased chance of lbw babies.…”
Section: Discussioncontrasting
confidence: 57%
“…6,10 The literature review performed for this study did not find any studies that had identified the relationship between LBW or PM and low educational level on the part of the IP, which was observed here. However, in a systematic review, the authors found an association between BP or PM and the IP's profession -increased risk was observed among workers in agriculture, industry and mining and among unemployed people, when compared with technicians or professionals requiring greater specialization.…”
Section: Discussionmentioning
confidence: 64%
“…This explains the fact that some studies have described positive associations between DV during pregnancy and LBW, prematurity (PM) or both, [3][4][5] while others have not found any association whatsoever. [6][7][8] Low birth weight can occur as a result of a whole range of biological, behavioral and socioeconomic factors and can be understood as a direct or indirect consequence of these factors. The direct link between violence and LBW can be as a result of abdominal trauma, and the indirect, but no less severe, effects may be the result of drug and alcohol use, stressful conditions and inadequate nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes metodologias de pesquisa utilizadas podem contribuir para que essa relação permaneça desconhecida, uma vez que muitos dos resultados nĂŁo sĂŁo comparĂĄveis. Isso justifica o fato de que alguns estudos tĂȘm descrito associação positiva da VD durante o perĂ­odo gestacional com BPN, prematuridade (PM) ou ambos [3][4][5] , e outros nĂŁo encontraram qualquer associação [6][7][8] .…”
Section: Introductionunclassified